Question is attached​

Asked 9 months ago
Viewed 690659 times
1
Question is attached​

1 Answer

2

Hello!

\large\boxed{f^{-1} = \frac{5x+2}{4x-2}, f^{-1}(3) = \frac{17}{10} }

f(x) = \frac{2x +2}{4x - 5}

Find the inverse by swapping the x and y variables:

y = \frac{2x +2}{4x - 5}\\\\x = \frac{2y +2}{4y - 5}

Begin simplifying. Multiply both sides by 4y - 5:

x(4y - 5) = 2y + 2

Start isolating for y by subtracting 2 from both sides:

x(4y - 5) -2 = 2y

Distribute x:

4yx - 5x - 2 = 2y

Move the term involving y (4yx) over to the other side:

- 5x - 2 = 2y - 4yx\\\\

Factor out y and divide:

- 5x - 2 = y(2 - 4x)\\\\y = \frac{-5x-2}{-4x+2} \\\\y = \frac{-(5x + 2)}{-(4x - 2)} \\\\y^{-1} = \frac{5x + 2}{4x - 2}

Use this equation to evaluate f^{-1}(3)

f^{-1}(3) = \frac{5(3) + 2}{4(3) - 2}  = \frac{17}{10}

Edit
avatar
Onie Hayes
15.5k 3 10 26
answered 9 months ago